2023
DOI: 10.1002/nep3.22
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes in neonatal stroke and hypoxic‐ischemic encephalopathy: Pathophysiological mechanisms and therapeutic possibilities

Pedro M. Pimentel‐Coelho

Abstract: Neonatal arterial ischemic stroke (NAIS) and neonatal hypoxic‐ischemic encephalopathy (HIE) are common causes of neurological impairments in infants, for which treatment options are very limited. NAIS and HIE induce an innate immune response that involves the recruitment of peripheral immune cells, including monocytes, into the brain. Monocytes and monocyte‐derived cells have the potential to contribute to both harmful and beneficial pathophysiological processes, such as neuroinflammation and brain repair, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 148 publications
(343 reference statements)
0
4
0
Order By: Relevance
“…The variability in the cut-off values of markers such as NLR, PLR, and MLR across different clinics underscores the importance of contextual interpretation of these markers [20,21,24]. In our study, MLR demonstrated the most substantial predictive capability, suggesting its potential role as an efficacious tool in predicting critical clinical outcomes, facilitating early and precise interventions, and improving clinical outcomes in HIE patients.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The variability in the cut-off values of markers such as NLR, PLR, and MLR across different clinics underscores the importance of contextual interpretation of these markers [20,21,24]. In our study, MLR demonstrated the most substantial predictive capability, suggesting its potential role as an efficacious tool in predicting critical clinical outcomes, facilitating early and precise interventions, and improving clinical outcomes in HIE patients.…”
Section: Discussionmentioning
confidence: 73%
“…Elevated WBC counts further accentuate this inference, emphasizing a heightened systemic inflammatory response posthypoxia. The neutrophil/lymphocyte ratio, a prominent systemic inflammatory marker, showed significant shifts [17,[21][22][23], echoing the findings of several studies that validated its prognostic utility in various conditions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Monocyte-derived macrophages are involved in vascular repair, phagocytosis, immune regulation, and tissue repair (Milich et al, 2019). Their chronic recruitment to scars may have implications for the development of monocyte-based cell treatments (Garcia-Bonilla et al, 2018;Pimentel-Coelho, 2023) and immunotherapies (Rosenzweig et al, 2019).…”
Section: Discussionmentioning
confidence: 99%